The Remarkable Kinship of Marjorie Kinnan Rawlings and Ellen Glasgow - Lear, Ashley Andrews (Book collections on Project MUSE., 2018)
Ashley Lear's The Remarkable Kinship of Marjorie Kinnan Rawlings and Ellen Glasgow examines the documents collected by Rawlings on Glasgow, along with her personal notes, to better understand the experiences that brought these two women writers together and the importance of literary friendships between women writers. This study sheds new light on the complexities of their professional success and personal struggles, both of which led them to find friendship and sympathy with one another.